Study of Implementation of Agroforestry System in Cibulao Village, Bogor District, West Java Province - Antonius Eko Sunardi; Qonita Hasna’ul Aini; Muhammad Rizki Aditya; Sari Viciawati Machdum (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2018)
This study tries to explore how the implementation of the Agroforestry system that is initiated by the Ministry of Forestry. The study took place in Cibulao Village, Bogor District, West Java Province, which is in a forest area. The study approach is carried out qualitatively through in-depth interviews. The Agroforestry system is intended to try to reduce forest conversion and destruction as an alternative to protect the forest and at the same time give people around the forest an opportunity to exploit the economic potential of the forest.